THE ROLE OF SOCIAL INSTITUTIONS IN THE DEVELOPMENT OF WOMEN'S ENTREPRENEURSHIP IN UZBEKISTAN: PRACTICAL STEPS AND RESULTS (The Conference Hub, 2025)
In Uzbekistan, efforts are being made to increase women's economic activity, encourage them to engage in entrepreneurship, and ensure their employment. In particular, it is important to ensure the economic independence of women entrepreneurs by supporting their business ideas. In our country, specific measures have been established to provide organizational, socio-legal, financial, psychological, and other types of support to women. Over the past 5 years, the number of women entrepreneurs in Uzbekistan has doubled, and the number of women entrepreneurs who have started their own businesses has exceeded 205 thousand. In 2023 alone, more than 13 trillion soums in loans were allocated to more than 279 thousand entrepreneurial projects, and almost 300 billion soums in subsidies were allocated to almost 57 thousand women. In addition, about 200 thousand women were trained in professions and entrepreneurship. Most importantly, more than 400 thousand of our sisters were provided with jobs.